2013
DOI: 10.1055/s-0038-1623684
|View full text |Cite
|
Sign up to set email alerts
|

Okuläre Veränderungen bei chronischer Niereninsuffizienz und/oder systemischer Hypertension der Katze

Abstract: Zusammenfassungder Studie war zu prüfen, ob der Grad der Niereninsuffizienz bzw. die Höhe des Blutdrucks bei Katzen mit chronischer Niereninsuffizienz (CNI) eine Aussage hinsichtlich der Ausprägung von Fundusveränderungen zulässt und ob die Blutdruckhöhe bei verschiedenen mit Hypertension assoziierten Erkrankungen differiert.Bei Katzen mit CNI und/oder hypertensiver Retinopathie sowie gesunden Katzen erfolgten eine klinische Allgemeinuntersuchung, eine ophthalmologische Untersuchung, eine Blutdruckmessung mitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Applanation tonometry is considered to underestimate IOP values. 35 Therefore, because of the similarity to the IOP values determined by von Spiessen et al 34 the results of the present study can be considered reliable and applicable in routine healthcare for older cats.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Applanation tonometry is considered to underestimate IOP values. 35 Therefore, because of the similarity to the IOP values determined by von Spiessen et al 34 the results of the present study can be considered reliable and applicable in routine healthcare for older cats.…”
Section: Discussionsupporting
confidence: 81%
“…This value was significantly lower than the mean IOP (20.74 mmHg) obtained by Rusanen et al using rebound tonometry in healthy cats (mean age 42 months) ( P <0.001), 24 and was equal to the values obtained by von Spiessen et al (16.7 ± 3 mmHg). 34 Only one other study evaluated IOP in older cats (mean age 12.3 ± 2.9 years) using applanation tonometry. The mean IOP was 12.3 ± 4 mmHg and IOP decreased with increasing age.…”
Section: Discussionmentioning
confidence: 99%
“…The TVP includes specific settings for cats ('feline') and rabbits ('lapine') in addition to dogs ('canine') and horses ('equine'), whereas the TV01 only has specific calibrations for dogs ('d' mode) and horses ('h' mode); thus, previous validation studies in cats have been done using the 'd' mode, which is the closest setting to cats. A previous study found that inaccurate readings may be obtained when the TV01 is not used at the correct distance (4-8 mm) from the cornea or when the probe is not perpendicular to the axial cornea, 33 thus features meant to safeguard against acquiring inaccurate readings due to improper tonometer position have been incorporated in the TVP. If the TVP is not held at an appropriate distance from the cornea, messages indicating "too near" or "too far" will appear on the instrument screen; if the TVP is not in the correct orientation, an illuminating ring surrounding the probe collar (or the upper left and lower right corners of the screen when probe collar illumination is turned off) will change from green to red.…”
Section: Introductionmentioning
confidence: 99%